Identifikasi Kualitas Air Sumur Berdasarkan Kandungan Logam Berat Menggunakan Spektrofotometri Serapan Atom di Desa Lamakera Kabupaten Flores Timur - Ibrahim, Dewi Kartika Sari; Fuadi, Nurul; Jumardin, Jumardin; Wahyullah, Wahyullah (Journal of Health, Education, Economics, Science, and Technology, 2025)
A study was conducted to identify heavy metals iron or Ferrum (Fe), Cadmium (Cd), and copper or Cuprum (Cu) based on the depth of well water using atomic absorption spectrophotometry method, pH test of water by measuring using digital pH meter and water turbidity using Turbidity meter with NTU (Nephelometric Turbidity Unit) unit in Lamakera Village, East Flores Regency. The purpose of this study was to determine the content of heavy metal elements, pH content and turbidity of the well water. The results showed that the analysis of heavy metal content in well water had the same levels in wells A (10 m), B (25 m), and C (15 m). The levels are Fe < 0.03 mg/L, Cd < 0.0007 mg/L, and Cu < 0.010 mg/L as well as the average pH content in well A on the surface is 6.99 and the base is 6.63. Well B on the surface is 6.34 and the base is 6.29. Well C surface 6.45 and base 6.56. The turbidity of well A at the surface is 0.93 NTU and the bottom is 0.66 NTU. Well B at surface 0.6 NTU and bottom 0.86 NTU. Well C at surface 0.8 NTU and bottom 0.86 NTU.